A memória imagética pelo UHE Belo Monte (PA) narrado por mulheres arpilleristas - PORTUGAL, Jéssica Feiteiro (Universidade Federal do Pará, 2020)
This academic work speaks about a reflection from the social and environmental impacts resulting of the process of implantation of hydroelectric plants in the Amazon, through a Chilean embroidery technique of cloth fabric making, produced and exposed by women affected by UHE Belo Monte (PA). Methodologically, reflection starts from the perception of the landscape represented by arpilleras not only by the iconographic aesthetics of the image, but as an imaginary narrative, which is subjectively articulated by arpilleristas women, is a product of the collective imaginary, and thus materializes through discourse Ideological resistance to the impacts caused by the enterprise. As a way to guide the reflection of the image understood as narrative and memory product, this study is based on the theoretical-methodological articulation of authors that approach the subject of: Imagem fotográfica como método etnográfico como Guran (2011); O imaginário coletivo por Maffesoli (2001); A memória coletiva por Halbwachs (1968). The analysis makes the possibility to perceive the image that the arpilleristas women affected by the Belo Monte Hydroelectric Plant seek to explain about the process of implantation of hydroelectric plants in the Amazon from the social representation, and the reasons that justify the creative use of the art by images as language strategy and communication.